The Relationship between Socio- Spatial and Elderly Cultural Values Towards a Sustainable Senior Retirement Housing - Ismail, Alice Sabrina; Zamry, Muhammad Nor Haziq (International Journal of Psychosocial Rehabilitation, 2020)
The elderly community indicates a rising population growth each year in developing regions which projecting these states to become an aging nation between the year 2020 to 2040. Nonetheless, there is less consideration given by the responsible parties in advocating a better-built environment focusing on elderly housing to cater to the aging community needs. Past literature, however, much focuses on the problems and challenges from the perspective of social and economic policy programs rather than dwell into the aspect of elderly living. So far there has been no literature that addresses the aspects of best practices relating to elderly retirement housing design principles which emphasize the concept of flexible home care with consideration on the integration of cultural values and socio-spatial in elderly homes. The objective of this study is to firstly identify issues relating to the current elderly housing design from the cultural perspective and secondly, to propose design referential study, methods involving questionnaire and interview of elderly residents living in existing elderly housing are studied to establish the determinants for the elderly housing design that concerns on cultural factors involving the value of preserving dignity and manners, the value of community spirit and compliance as well as the value of spiritual wellbeing and harmony. Findings indicate that decent, better quality and appropriate design of elderly housing considering cultural values mentioned above are vital in improving their life quality in terms of comfort and safety for fostering sustainable living. Therefore, the provided guidelines from the best design practices will give benefits for future designers and related authorities to improve the design quality of elderly housing as well as help reduce pitfall among the home's providers for the elderly in Malaysia.